Ranking of universities using dichotomous tests - Gudelytė, Laura; Krylovas, Aleksandras; Laukevičius, Tadas (Lietuvos matematikos rinkinys, 2012)
This article presents the application of the generalized dichotomous test methodologies in the rating of Universities. More as compared to previous amount of available statistical information is used in this case. In addition, the authors seek to develop an algorithm which automatically calculates and clusters statistical data. As an example the authors take the Vilnius city neighborhoods. New algorithms will accurately cluster Vilnius neighborhoods by the normalized price.